Recent Developments in Halide Perovskite Nanocrystals for Indirect X-ray Detection - Balitskii, Olexiy; Sytnyk, Mykhailo; Heiß, Wolfgang (Advanced Materials Technologies, 2024)
Metal halide perovskites are revolutionizing X-ray detection through a combination of low cost, solution processing, favorable optoelectronic properties, and high stopping power for high-energy ionizing radiation. While perovskite single crystals and polycrystalline wafers are considered direct X-ray converters, most medical X-ray applications are based on scintillators that shift high-energy radiation into the visible. Several materials are on the market, but demonstrations based on CsPbBr3 nanocrystals, possibly embedded in a matrix material or combined with organic molecules as luminescent species, highlight their competitiveness with established scintillators in terms of radioluminescence yield and transient behavior. Major hurdles that perovskite nanocrystal scintillators must overcome are environmental stability and toxicity. While there are still few examples of high-performance lead-free perovskite nanocrystal scintillators, microcrystalline perovskites are emerging with promising properties, reduced toxicity, and significant Stokes shifts to avoid reabsorption of emission in thick films. Thus, the near future of perovskite nanocrystal scintillator materials will primarily be the adoption of recipes for materials with proven properties in microcrystalline form. The nanocrystal colloidal solutions will facilitate the large-scale printing of homogeneous and scattering-free films to obtain high contrast and spatial resolution X-ray images by scintillation.
CRIS-Team Scopus Importer:2024-06-07
Keywords: halide perovskites; lead-free; nanocrystals; scintillators; Stokes shift